2017
DOI: 10.1016/j.jpowsour.2017.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of iron and copper doped manganese cobalt spinel oxides as protective coatings for solid oxide fuel cell interconnects

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 58 publications
(85 reference statements)
7
59
1
1
Order By: Relevance
“…This suggests that in order to lower the ASR reducing the oxidation rate of the alloy is more important than increasing the conductivity of the coating material. We have previously shown that the MC, Fe3 and Cu3 materials result in nearly the same ASR after more than 4000 h oxidation at 800 °C when applied as a coating on Crofer 22 APU [28,30].…”
Section: Suitability As Sofc Interconnect Coating Materialsmentioning
confidence: 90%
See 1 more Smart Citation
“…This suggests that in order to lower the ASR reducing the oxidation rate of the alloy is more important than increasing the conductivity of the coating material. We have previously shown that the MC, Fe3 and Cu3 materials result in nearly the same ASR after more than 4000 h oxidation at 800 °C when applied as a coating on Crofer 22 APU [28,30].…”
Section: Suitability As Sofc Interconnect Coating Materialsmentioning
confidence: 90%
“…The most widely studied compositions in this system are Mn1.5Co1.5O4 and MnCo2O4. Although these materials are not stable under the reducing conditions found on the anode side of the SOFC, they are considered promising coatings for the cathode side, where they limit Cr-volatilization and reduce the oxidation rate of the FSS [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…With regards to the coating materials, spinel coatings have received significant attention [9,10]. Different spinel compositions have been analysed to find optimal protective-conductive layers for SOFC interconnects with low oxidation rate, low contact resistance, low electrical resistance, high adhesion, and, above all, low release rates of chromium [11][12][13]. Larring and Norby proposed (Mn, Co)3O4 as the promising candidate for the protective layer application for metallic SOFC interconnects (CFY alloy) [14].…”
Section: Different Coating Techniques Can Be Broadly Classified As Vamentioning
confidence: 99%
“…At room temperature, spinel (Mn, Co)3O4 consists of a mixture between the tetragonal structure Mn2CoO4 and cubic structure MnCo2O4 phases. During heat treatment, the temperature increase around 400 °C makes the cubic structure stable [8,25,26,55,56]. Thus, under working conditions of SOFC's, around 800 °C, the only structure present is the cubic.…”
Section: X-ray Diffractionmentioning
confidence: 99%